Aspek Hukum Terkait Kegiatan Penagihan oleh Debt Collector dalam Kegiatan Perbankan dan Lembaga Keuangan Lainnya di Indonesia - Albertus Magnus Barlenando Yusuf Hura (UNES Law Review, 2023)
Banks and/or other financial service institutions that provide credit have a risk of problems, such as bad credit. This is what makes Banks and/or other Financial Services Institutions use Debt Collector Services to carry out collections to obtain payments. However, in terms of collections carried out by Collection Services or Debt Collectors, it sometimes causes problems in the community. This raises questions in this research related to: how to apply Debt Collector services in dealing with problematic credit customers and to what extent is the effectiveness of using Debt Collector services in collecting problematic credit customers. Therefore, doctrinal research methods are needed to answer these questions.